2022
DOI: 10.1186/s13054-022-03957-7
|View full text |Cite|
|
Sign up to set email alerts
|

Pain and sedation management and monitoring in pediatric intensive care units across Europe: an ESPNIC survey

Abstract: Background Management and monitoring of pain and sedation to reduce discomfort as well as side effects, such as over- and under-sedation, withdrawal syndrome and delirium, is an integral part of pediatric intensive care practice. However, the current state of management and monitoring of analgosedation across European pediatric intensive care units (PICUs) remains unknown. The aim of this survey was to describe current practices across European PICUs regarding the management and monitoring of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 45 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors identified an error in the author name Marco Daverio. The given name and family name were erroneously transposed.…”
Section: Correction To: Critical Care (2022) 26:88 101186/s13054-022-...mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author name Marco Daverio. The given name and family name were erroneously transposed.…”
Section: Correction To: Critical Care (2022) 26:88 101186/s13054-022-...mentioning
confidence: 99%
“…The survey included single‐ and multiple‐choice closed‐ended questions to facilitate analyses and comparisons, as well as free‐text questions to allow the extrapolation of more detailed information. The first part of the survey was dedicated to define the analgesia and sedation practices in Europe and was previously published 15 . The second part of the survey is presented here and consisted of 11 overlapping questions with the first survey on PICU characteristics, and another 32 questions organized within the following sections: Section 1: practices related to the analgosedation weaning and IWS prevention; Section 2 : diagnosis and management of IWS and delirium; and Section 3 : practices related to early mobilization (Appendix S1).…”
Section: Methodsmentioning
confidence: 99%
“…Many repeated pain stimuli will cause stress reactions to the body, leading to a series of short-term and long-term adverse effects on neonates. [ 6 8 ]…”
Section: Introductionmentioning
confidence: 99%